Alginate based scaffolds for bone tissue engineering - Valente, Joana (2018)
Submitted by Ilídio Correia (icorreia@ubi.pt) on 2018-03-19T14:10:45Z No. of bitstreams: 1 2012 Valente MSEC.pdf: 1179451 bytes, checksum: b26ccdfe6acebbc1b7926fa82f72c6f5 (MD5)